2023
DOI: 10.1186/s12981-023-00510-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose trajectories and incidence of diabetes mellitus in Ugandan people living with HIV initiated on dolutegravir

Abstract: Background Following reports of anti-retroviral therapy (ART) experienced Ugandan people living with HIV (PLHIV) presenting with diabetic ketoacidosis weeks to months following a switch to dolutegravir (DTG), the Uganda Ministry of Health recommended withholding DTG in both ART naïve and experienced PLHIV with diabetes mellitus (T2DM), as well as 3-monthly blood glucose monitoring for patients with T2DM risk factors. We sought to determine if the risk of T2DM is indeed heightened in nondiabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
(35 reference statements)
3
15
0
Order By: Relevance
“…Additionally, Odenyo et al; found that overweight patients were 1.7 times more likely to develop hyperglycemia. In terms of BMI for age z scores, the current study’s findings align with studies by Namara et al; and the GLUMED study in Kampala, which also did not find a significant association between BMI and hyperglycemia (20,26). The duration on Dolutegravir also did not show a statistically significant association with hyperglycemia in contrast to the findings by Lamorde et al; in Uganda (5).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, Odenyo et al; found that overweight patients were 1.7 times more likely to develop hyperglycemia. In terms of BMI for age z scores, the current study’s findings align with studies by Namara et al; and the GLUMED study in Kampala, which also did not find a significant association between BMI and hyperglycemia (20,26). The duration on Dolutegravir also did not show a statistically significant association with hyperglycemia in contrast to the findings by Lamorde et al; in Uganda (5).…”
Section: Discussionsupporting
confidence: 90%
“…Over the same period, he experienced worsening insulin resistance and concurrent increase in pancreatic beta cell function which could have been compensatory. Much as the worsening insulin resistance could be attributed to the weight gain, on evaluation of glucose changes in the whole study cohort, there was signi cant improvement in blood glucose despite a signi cant increase in BMI over the 48 weeks of follow up [9]. This may suggest that this patient had an inherent risk of developing T2DM, independent of weight gain and exposure to DTG.…”
Section: Discussionmentioning
confidence: 93%
“…This 44-year-old man was enrolled in a prospective cohort study (GLucose Metabolism changes in Ugandan HIV patients on Dolutegravir, GLUMED study) evaluating glucose metabolism changes in antiretroviral therapy (ART) naïve Ugandan people with HIV (PWH) on tenofovir/ lamivudine/ dolutegravir (TDF/3TC/ DTG) for 48 weeks [9]. Patients underwent serial 2-hour oral glucose tolerance tests (OGTTs) at baseline, 12 and 36 weeks.…”
Section: Case Presentationmentioning
confidence: 99%
“…2) Most patients presenting with accelerated hyperglycemia are heavily ART experienced before switch to dolutegravir or other integrase inhibitors [11], [28]- [30], [32]. 3) In ART naïve Ugandan patients on dolutegravir, the incidence of diabetes mellitus is very low, comparable to safety data results in landmark DTG trials and largely less than in most cohort studies in Europe and North America [15]. 4)…”
Section: Discussionmentioning
confidence: 95%